Perancangan Sistem Administrasi Manajemen Tanaman Hias di Win’s Cultura Pondok Cabe Berbasis Android - Muhammad Fadly; Muhammad Pasya Ariq; Ricky Wijaya; Wasis Haryono (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Ornamental Plant Marketing is currently experiencing various increases in sales. This increase in sales makes us think that the marketing of plants at WIN'S CULTURA currently requires a new innovation in managing marketing, which currently at WIN'S CULTURA still uses a marketing system that manually comes directly to the store, this makes marketing in ornamental plant products are less efficient in our opinion. In this step of making efficiency in the marketing management of ornamental plants, we design a management administration application system, which in the application we make can be useful in providing information related to ornamental plant products, with this limited information in marketing and selling ornamental plant products can be overcome and can also improve service to buyers to make purchases with the ornamental plant marketing management system based on the android application that we made and our hope in making this application is that this marketing management application system will be able to help work efficiency and effectiveness for our clients. The object of research that we are investigating is related to the use and design of android-based applications as a system or option for our clients in marketing their agricultural products in the form of ornamental plants, toga plants, fruits and others.